Reines Bewusstsein und Bewusstseinskultur. Eine kritische Anfrage an Thomas Metzinger - Schöllhorn-Gaar, Patricia (Zeitschrift für Theologie und Philosophie, 2026)
In The Elephant and the Blind, Thomas Metzinger examines mystical experiences or "experiences of pure consciousness". He interprets them as experiences without positive perceptual content and claims that they should be the foundation for establishing a new culture. He calls this new culture a "Bewusstseinskultur" (culture of consciousness). However, the question arises as to whether Metzinger’s interpretation of pure consciousness experiences as experiences without positive perceptual content is at all compatible with establishing a "Bewusstseinskultur". To answer this question, I will show a) how the concepts of "pure consciousness" and "Bewusstseinskultur" are defined, b) how Metzinger interprets the lack of a positive perceptual content, and c) whether this interpretation is compatible with the intention of establishing a "Bewusstseinskultur". I argue that the lack of a positive perceptual content ultimately represents a lasting challenge for Metzinger.